The role of the university research laboratory in technology transfer to firms in Brazil: Two case studies in biotechnology. Issue 4 (August 2022) - Liboreiro, Karla Rocha; Corradi, Ariane A; Rapini, Márcia Siqueira
This paper analyzes the role of the university research laboratory in university–industry interactions for technology transfer. Specifically, it examines how the laboratory research infrastructure, team qualification and local incentives influence knowledge and technology transfer in biotechnology. Despite the importance of the research laboratory for an entrepreneurial university and the development of new technologies, few studies have focused on this level of analysis. This research addresses this literature gap with data from two leading laboratories in a highly-ranked Brazilian university. Data were collected through questionnaires on laboratory infrastructure and channels of collaboration with firms, interviews with laboratory leaders and key post-doc fellows, and documentary research. The results show that physical infrastructure, biological samples and qualified teams enabled technology transfer to firms. The main channel of interaction between these laboratories and firms is the generation of spin-offs, which perform the bilateral hybrid function of disseminating university research results and brokering patent licensing to larger firms. Spin-offs also contribute to the absorptive capacity of larger firms and, above all, allow laboratories to disclose results to the community and potential end-users. The findings present a new perspective on spin-off technology transfer in Brazil and open new research avenues for other developing countries.